Strengthening SDGs Through Islamic Financing in Banyu Biru Village, Central Java - Suprianto, Edy; Shodiq, Muhammad Jafar; Sulistyo , Heru; Saputri, Pungky Lela; Hamdan, Haslenna (LifeSciFi, 2024)
The integration of Islamic financing in Banyu Biru Village has yielded impressive results, driving sustainable development and empowering the community. This approach has spurred economic growth while fostering social equity, environmental stewardship, and a sense of shared responsibility among residents. Notable achievements include the expansion of organic farming through interest-free loans and profit-sharing, the advancement of renewable energy projects, and the empowerment of marginalized groups via benevolent loans. Additionally, Islamic finance has encouraged collaboration among entrepreneurs with profit-sharing models and supported investments in cultural preservation. This financial model has also strengthened governance and accountability structures, boosting the village's resilience against economic shocks and fluctuations. Banyu Biru stands as a model of ethical and inclusive development, demonstrating the transformative potential of Islamic financing. By integrating economic, social, and environmental goals, the village exemplifies how Islamic finance can build resilient, sustainable communities committed to achieving multiple Sustainable Development Goals (SDGs). Through its success, Banyu Biru highlights the ability of Islamic finance to address complex socio-economic challenges, offering a blueprint for other communities seeking to develop sustainably and inclusively.